Growth of metal-metal oxide nanostructures on freestanding graphene paper for flexible biosensors - Xu, Rong (2013)
Flexible biosensors are of considerable current interest for the development of portable point-of-care medical products, minimally invasive implantable devices, and compact diagnostic platforms. A new type of flexible electrochemical sensor fabricated by depositing high-density Pt nanoparticles on freestanding reduced graphene oxide paper (rGOP) carrying MnO2 nanowire networks is reported. The triple-component design offers new possibilities to integrate the mechanical and electrical properties of rGOP, the large surface area of MnO2 networks, and the catalytic activity of well-dispersed and small-sized Pt nanoparticles prepared via ultrasonic-electrodeposition. The sensitivity and selectivity that the flexible electrode demonstrates for nonenzymatic detection of H2O2 enables its use for monitoring H2O2 secretion by live cells. The strategy of structurally integrating metal, metal oxide, and graphene paper will provide new insight into the design of flexible electrodes for a wide range of applications in biosensing, bioelectronics, and lab-on-a-chip devices.